Ground-State Cooling of a Nanomechanical Resonator via Squeezed Light Injection in a Resolved-Sideband Regime - Viktoria Sokolova; Igor Vasiliev; Natalya Pavlova (Yayasan Adra Karima Hubbi, 2026)
Ground-state cooling of nanomechanical resonators is a fundamental requirement for realizing high-fidelity quantum control, precision sensing, and coherent quantum information processing. Conventional resolved-sideband cooling has achieved remarkable progress; however, quantum back-action, optical losses, thermal fluctuations, and finite cavity linewidths continue to limit cooling performance under realistic experimental conditions. This study aimed to evaluate the effectiveness of squeezed light injection in enhancing ground-state cooling while investigating the interactions among optical squeezing, optomechanical coupling, cavity dynamics, quantum back-action suppression, and thermal phonon reduction within the resolved-sideband regime. A mixed-methods sequential explanatory design was employed using 14,000 large-scale optomechanical simulations complemented by experimental benchmark datasets, cavity calibration records, laboratory implementation reports, and expert evaluations. Quantitative data were analyzed through generalized linear mixed-effects modeling, Monte Carlo uncertainty estimation, sensitivity analysis, and multivariate statistical techniques, whereas qualitative evidence was interpreted using thematic analysis of experimental observations and technical documentation. Findings demonstrated that squeezed-light-assisted cooling significantly reduced the final mean phonon occupation, improved ground-state occupation probability, suppressed quantum back-action, preserved mechanical coherence, and enhanced cooling efficiency across multiple optomechanical configurations. Results indicate that engineered quantum fluctuations provide an effective mechanism for overcoming practical limitations associated with conventional sideband cooling. The proposed framework establishes a robust foundation for developing scalable optomechanical platforms supporting quantum sensing, hybrid quantum systems, precision metrology, and future quantum information technologies.